M-School Application Development As A Substitute Books Contact Between Parents And Teachers In Blossom Mobile Web-Based Preschool - Febri Dolis Herdiani (Institute of Computer Science (IOCS), 2018)
Blossom Preschool is a school for young children ranging from 2- 5 years of age. The method used is the approach centers or BCCT (Beyond center and Circle time). In this method, children are stimulated to actively carry out activities to play while learning in centers of learning such as the Center for Religion, Sentra Balok, Calculate Sentra, Sentra Art, Nature Sentra, Sentra Literacy, Computer Sentra. Preschool Blossom current constraints still use a book manual link in the process of recording information to parents so that the information should be written manually or printed manuals that allow for errors such as information that is exchanged, parents forget to read the book liaison and delivery of information takes a long time. To overcome this, then built M-School application form mobile web application. The design process is done using the waterfall process model is then applied in the form of coding program to produce applications that are ready to implement. With the construction of this application can help parents and teachers to communicate. Moreover, it can shorten the time simplify the process of sending information